Altered activation in sensorimotor network after applying rTMS over the primary motor cortex at different frequencies. Issue 7 (7th June 2020) - Wang, Xiaoyu; Li, Lingyu; Wei, Wei; Zhu, Tingting; Huang, Guo‐Feng; Li, Xue; Ma, Hui‐Bin; Lv, Yating
Abstract: Introduction: Repetitive transcranial magnetic stimulation (rTMS) over the primary motor cortex (M1) can modulate brain activity both in the stimulated site and remote brain areas of the sensorimotor network. However, the modulatory effects of rTMS at different frequencies remain unclear. Here, we employed finger‐tapping task‐based fMRI to investigate alterations in activation of the sensorimotor network after the application of rTMS over the left M1 at different frequencies. Materials and Methods: Forty‐five right‐handed healthy participants were randomly divided into three groups by rTMS frequency (HF, high‐frequency, 3 Hz; LF, low‐frequency, 1 Hz; and SHAM) and underwent two task‐fMRI sessions (RH, finger‐tapping with right index finger; LH, finger‐tapping with left index finger) before and after applying rTMS over the left M1. We defined regions of interest (ROIs) in the sensorimotor network based on group‐level activation maps (pre‐rTMS) from RH and LH tasks and calculated the percentage signal change (PSC) for each ROI. We then assessed the differences of PSC within HF or LF groups and between groups. Results: Application of rTMS at different frequencies resulted in a change in activation of several areas of the sensorimotor network. We observed the increased PSC in M1 after high‐frequency stimulation, while we detected the reduced PSC in the primary sensory cortex (S1), ventral premotor cortex (PMv), supplementary motor cortex (SMA), and putamen after low‐frequency stimulation. Moreover, the PSC in the SMA, dorsal premotor cortex (PMd), and putamen in the HF group was higher than in the LF group after stimulation. Conclusion: Our findings suggested that activation alterations within sensorimotor network are dependent on the frequency of rTMS. Therefore, our findings contribute to understanding the effects of rTMS on brain activation in healthy individuals and ultimately may further help to suggest mechanisms of how rTMS could be employed as a therapeutic tool. Abstract : Repetitive transcranial magnetic stimulation (rTMS) over the primary motor cortex (M1) could modulate the activity both in the stimulated site and remote brain regions of the sensorimotor network. We employed finger‐tapping task‐based fMRI to investigate the altered activations of the sensorimotor network after the application of rTMS over the left M1 at different frequencies.